Luang Prabang, sanctuaire Unesco et paradis gay - David Berliner (Genre, Sexualité et Société)
Luang Prabang is a town in Northern Laos that has been on the World Heritage List since 1995. Famous for its Buddhist monasteries and orange-robed monks, as well as for its colonial architecture, its international reputation has grown quickly. It has now become a key destination for tourists in Southeast Asia. Among the unexpected effects of UNESCO recognition and the attendant tourist boom, Luang Prabang is now described by some of its inhabitants and tourists as a town that has become gay (although men slept with men in Laos long before the advent of tourism and heritage-making). There is, indeed, another Luang Prabang, the “gay paradise”, seen as indecent by most locals and which represents the other facet of the town of tradition, monks and “pure” women.